Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep33935
|View full text |Cite
|
Sign up to set email alerts
|

A novel affinity-based method for the isolation of highly purified extracellular vesicles

Abstract: Extracellular vesicles (EVs) such as exosomes and microvesicles serve as messengers of intercellular network, allowing exchange of cellular components between cells. EVs carry lipids, proteins, and RNAs derived from their producing cells, and have potential as biomarkers specific to cell types and even cellular states. However, conventional methods (such as ultracentrifugation or polymeric precipitation) for isolating EVs have disadvantages regarding purity and feasibility. Here, we have developed a novel meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
285
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(293 citation statements)
references
References 32 publications
(42 reference statements)
5
285
1
2
Order By: Relevance
“…Immunoprecipitation using antibodies against exosome surface proteins can alleviate this problem and even separate exosomes derived from different cell types. However, the yield is usually lower than with centrifugation techniques and often compromises a quantitative analysis of exosome function (Brett et al, 2017; Momen-Heravi et al, 2013; Nakai et al, 2016; Szatanek, Baran, Siedlar, & Baj-Krzyworzeka, 2015). Recently, great strides were made in the field of exosome isolation introducing new techniques such as ultrafiltration and microfluidics-based separation.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…Immunoprecipitation using antibodies against exosome surface proteins can alleviate this problem and even separate exosomes derived from different cell types. However, the yield is usually lower than with centrifugation techniques and often compromises a quantitative analysis of exosome function (Brett et al, 2017; Momen-Heravi et al, 2013; Nakai et al, 2016; Szatanek, Baran, Siedlar, & Baj-Krzyworzeka, 2015). Recently, great strides were made in the field of exosome isolation introducing new techniques such as ultrafiltration and microfluidics-based separation.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…Using antibodies raised against the mammalian proteins, neither CD81 nor CD63 displayed any immunoreactive bands in A1 cells or EVs. Our Western blot results were further verified using FACS analysis with EV capture beads in which Tim4 was used to bind all vesicles containing exposed phosphatidyl serine [46] and then probed for surface protein phenotypes with labelled antibodies. High levels of TSP1 were quantitated in A1-EVs (~99%) with a lower abundance observed in NHDF-EVs at ~47% (Figure 5(i)).…”
Section: Resultsmentioning
confidence: 75%
“…A few studies have also reported that PS expression on the membrane leaflet is more abundant in cancer cells and cancer cell derived exosomes compared to those from healthy controls. In order to detect and quantify the PS expression on cells or vesicle surfaces, several proteins have been tested and specific binding affinities of Tim4 and annexin V to PS have been proved. One of the most widely studied PS‐binding molecules, annexin V, is a 35.8 kDa protein which binds PS in a calcium‐dependent manner .…”
Section: Introductionmentioning
confidence: 99%